Periodontitis como factor de riesgo para preeclampsia - Gallardo Plasencia, Alexandra Paola (2017)
Objective: To evaluate whether periodontitis is a risk factor for preeclampsia. Material and Methods: An analytical retrospective case-control study was conducted. Case group: 12 pregnant women with preeclampsia and the control group: 114 pregnant women without preeclampsia. Both groups were attended at the Belen Hospital of Trujillo during the period August-October 2015. The information was obtained from the medical history and the periodontogram on the data collection tab. Descriptive and analytical statistics were used to process the data. The calculation of the Odds ratio determined the strength of association of periodontitis for preeclampsia, value <0.05. Results and conclusions: The data obtained were processed in an Excel spreadsheet and analyzed with the statistical analysis program SPSS v. 22, resulting in an OR = 3.75 with 95% CI = [1.1094-12.6753] for a p = 0.0334, with which it can be concluded that periodontitis increases the risk of preeclampsia by 3.75 times more. The chi-square test was performed = 3.55, so we can affirm that there is a 90% probability that there is an association between periodontitis and preeclampsia